Hard coating, preparation method of hard coating, flexible gear and application of flexible gear

By forming a hard coating of the inner layer of metal elements and carbon doped molybdenum -doped molybdenum layers on the surface of the soft wheel parts, the problem of insufficient friction and wear performance of the soft wheel parts in existing technologies, and realizing high -precision maintenance and length The effect of life.

CN119372596APending Publication Date: 2025-01-28GUANGDONG JIYA PRECISION MASCH TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411499906.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing coatings cannot effectively improve the friction and wear performance of soft wheel parts, resulting in insufficient service life and accuracy retention of the harmonic reducer.

Method used

Design a hard coating, including the inner layer of the metal element and the outer layer of carbon doped molybdenum, and form the surface of the substrate through the magnetic sputtering process to enhance the binding force of the coating and the substrate and achieve excellent ones. Defaming wear -resistant effect.

Benefits of technology

The substrate surface friction coefficient and low wear rate are achieved, ensuring the low wear, high accuracy maintenance and long life characteristics of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372596A_ABST
    Figure CN119372596A_ABST
Patent Text Reader

Abstract

The invention discloses a hard coating, a preparation method of the hard coating, a flexible gear and application of the flexible gear, and relates to the technical field of coating materials. The hard coating is arranged on a base material and comprises an inner layer and an outer layer which are arranged in sequence, the components of the inner layer comprise metal elements, and the components of the outer layer comprise carbon-doped molybdenum disulfide; and the inner layer is close to the surface of the base material. The hard coating disclosed by the invention has excellent antifriction and wear-resistant effects, not only can enable a base material to have excellent dimensional stability before and after a coating process, but also has good binding force with the base material, is not easy to fall off in actual work, and can effectively reduce the wear rate of the flexible gear when being applied to the flexible gear, so that the service life of the flexible gear is prolonged. Therefore, the harmonic speed reducer has the advantages of long service life, low abrasion, high precision retentivity and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating materials, and in particular to a hard coating, a flexible wheel, and a preparation method and application thereof. Background Art

[0002] Harmonic reducers have the characteristics of compact structure, light weight, strong load-bearing capacity, and high transmission precision, and are widely used in the fields of robotic automation, aerospace, etc. The flexspline is the core part of the harmonic reducer product, and its friction and wear performance plays an important role in the life and precision retention performance of the reducer.

[0003] After the raw material bar forging, heat treatment and machining, the flexible wheel parts of the harmonic reducer are generally coated on the surface for strengthening treatment, thereby improving the fatigue strength of the tooth root of the flexible wheel parts. However, in addition to fatigue performance, the friction and wear performance of the flexible wheel parts is also crucial to the service life and precision retention of the harmonic reducer. It directly affects the friction and wear behavior of the two key friction pairs, the inner wall of the flexible wheel and the outer ring of the flexible bearing, and the tooth surface of the flexible wheel and the tooth surface of the rigid wheel, during service. However, the existing coatings cannot currently meet the needs of both improving the wear resistance of the flexible wheel parts to achieve high precision retention and ensuring long service life. Summary of the invention

[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a hard coating, which is designed to have an inner layer including a metal element and an outer layer including carbon-doped molybdenum disulfide, so that the formed hard coating has excellent friction reduction and wear resistance, good friction and wear performance, and good bonding with the substrate.

[0005] A second object of the present invention is to provide a method for preparing a hard coating.

[0006] A third object of the present invention is to provide a flexible spline.

[0007] A fourth object of the present invention is to provide a harmonic reducer.

[0008] The first aspect of the present invention provides a hard coating, which is arranged on a substrate and includes an inner layer and an outer layer arranged in sequence; the composition of the inner layer includes metal elements, and the composition of the outer layer includes carbon-doped molybdenum disulfide; the inner layer is close to the surface of the substrate.

[0009] The hard coating according to the embodiment of the present invention has at least the following beneficial effects:

[0010] The inner layer of the hard coating includes metal elements, and the outer layer includes carbon-doped molybdenum disulfide. The inner layer plays the role of a transition layer, and the outer layer plays the role of reducing friction and wear resistance. Using the inner layer containing metal elements as a transition layer can enhance the bonding force between the coating and the substrate, and has a good bonding effect. The outer layer, as a friction-reducing and wear-resistant layer, has carbon and molybdenum disulfide as the main components, combining the advantages of both, with high hardness, good wear resistance, and good friction and lubrication properties.

[0011] Due to the anti-friction and wear-resistant effect of the outer layer, the surface friction coefficient and wear rate of the substrate with the hard coating applied are small, which can reduce the negative impact of long-term wear accumulation on the product. Before and after the corresponding process of applying the hard coating to the substrate, the substrate has excellent dimensional stability, thereby ensuring that the product has the characteristics of low wear, high precision retention and long life.

[0012] According to some embodiments of the present invention, the outer layer has the following element composition, in atomic percentage: C: 50-80%, Mo: 15-30%, S: 4-12%, and the remaining elements are <10%.

[0013] Here, the remaining elements refer to other impurity elements that are inevitably present in the outer layer.

[0014] According to some embodiments of the present invention, the thickness of the outer layer is 2-3 μm.

[0015] According to some embodiments of the present invention, the inner layer has a thickness of 0.5 to 1 μm.

[0016] According to some embodiments of the present invention, the metal element of the inner layer includes at least one of titanium, chromium, nickel and aluminum.

[0017] According to some embodiments of the present invention, the nanoindentation hardness of the outer layer is 4 to 7 GPa.

[0018] According to some embodiments of the present invention, the load required for the hard coating to fail in adhesion is 40-60N.

[0019] According to some embodiments of the present invention, the friction coefficient of the hard coating is 0.04 to 0.06.

[0020] The second aspect of the present invention provides a method for preparing the hard coating according to the first aspect of the present invention, comprising the following steps:

[0021] A substrate is provided, and the inner layer and the outer layer are sequentially formed on the surface of the substrate by magnetron sputtering.

[0022] The method for preparing the hard coating according to the embodiment of the present invention has at least the following beneficial effects:

[0023] The preparation method of the hard coating is simple to operate and easy to control. By combining the above surface coating method, a hard coating with excellent friction reduction and wear resistance and good bonding strength can be introduced on the surface of the substrate using a magnetron sputtering process, which is suitable for large-scale industrial production.

[0024] According to some embodiments of the present invention, the preparation method includes the following steps: providing a substrate, forming an inner layer on the surface of the substrate by magnetron sputtering a metal target, and then simultaneously magnetron sputtering a graphite target and a molybdenum disulfide target to form an outer layer.

[0025] According to some embodiments of the present invention, the target material of the inner layer magnetron sputtering includes a metal target material; the magnetron sputtering conditions of the metal target material satisfy at least one of the following a) to c):

[0026] a) DC bias voltage is 400~600V;

[0027] b) The working current is 1~3A;

[0028] c) The processing time is 1 to 2 hours.

[0029] According to some embodiments of the present invention, the target material for magnetron sputtering of the outer layer includes a graphite target material; the magnetron sputtering conditions of the graphite target material satisfy at least one of the following d) to f):

[0030] d) The pulse bias voltage is 300-500V;

[0031] e) The working current is 1~2A;

[0032] f) The processing time is 3 to 5 hours.

[0033] According to some embodiments of the present invention, the target material for magnetron sputtering of the outer layer further comprises a molybdenum disulfide target material; the magnetron sputtering conditions of the molybdenum disulfide target material satisfy at least one of the following g) to i):

[0034] g) The pulse bias voltage is 300-500V;

[0035] h) The working current is 0.2~1A;

[0036] i) The processing time is 3 to 5 hours.

[0037] The third aspect of the present invention provides a flexible wheel, the surface of which is provided with the hard coating as described in the first aspect of the present invention, or the hard coating obtained by the preparation method described in the second aspect of the present invention.

[0038] The flexible wheel in the embodiment of the present invention has at least the following beneficial effects:

[0039] With the flexible wheel as the base material, a hard coating is applied on the surface of the flexible wheel. The hard coating has a high surface hardness and has excellent anti-friction and wear-resistant effects. The friction coefficient and wear rate of the flexible wheel containing the hard coating are reduced, and there is good bonding force between the flexible wheel and the hard coating, which ensures high-precision retention during application and improves durability.

[0040] A fourth aspect of the present invention provides a harmonic reducer, comprising the hard coating described in the first aspect of the present invention, or the flexible spline described in the third aspect of the present invention.

[0041] The harmonic reducer according to the embodiment of the present invention has at least the following beneficial effects:

[0042] The harmonic reducer contains a hard coating, which is applied to the flexible wheel. During the operation of the harmonic reducer, the hard coating has moderate hardness and anti-friction and wear-resistant effects, and is not easy to fall off, which effectively reduces the wear rate of the flexible wheel parts and reduces the accuracy degradation rate after durability, so that the harmonic reducer has the characteristics of long life, low wear and high precision retention.

[0043] The fifth aspect of the present invention provides an industrial robot joint component, comprising the hard coating described in the first aspect of the present invention, or the flexible spline described in the third aspect of the present invention, or the harmonic reducer described in the fourth aspect of the present invention.

[0044] The harmonic reducer is a core component of an industrial robot, and its quality level directly determines the performance of the robot joint. The industrial robot joint includes the harmonic reducer, flexible wheel or hard coating of the present invention, and the durability and precision retention are improved, so the positioning accuracy and service life of the industrial robot are also improved.

[0045] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 It is a schematic structural diagram of a hard coating and a substrate combined in one embodiment of the present invention.

[0047] Figure 2 is a cross-sectional SEM image of a hard coating according to an embodiment of the present invention.

[0048] Figure 3 This is a physical picture of a flexible wheel in the prior art. DETAILED DESCRIPTION

[0049] Embodiments of the present invention are described in detail below. The embodiments described with reference to the accompanying drawings are exemplary and are only used to explain the present invention, but should not be construed as limiting the present invention.

[0050] In the description of this specification, the description with reference to the terms "some embodiments", "some examples", "some specific embodiments", "some examples" or "some specific examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0051] The term "friction reduction and wear resistance" refers to reducing the coefficient of friction and wear resistance.

[0052] The first aspect of the present invention provides a hard coating, which includes an inner layer and an outer layer arranged in sequence; the composition of the inner layer includes metal elements, and the composition of the outer layer includes carbon-doped molybdenum disulfide; the inner layer is close to the surface of the substrate.

[0053] In the present invention, the inner layer of the hard coating includes metal elements, and the outer layer includes carbon-doped molybdenum disulfide, wherein the inner layer serves as a transition layer, which can enhance the bonding strength between the coating and the substrate and has a good bonding effect, while the outer layer serves as a friction-reducing and wear-resistant layer, which combines the advantages of the carbon-based coating and the molybdenum disulfide coating and has the characteristics of high hardness, good wear resistance, and good friction and lubrication properties, that is, a low friction coefficient.

[0054] Due to the anti-friction and wear-resistant effect of the outer layer of the hard coating, the surface friction coefficient and wear rate of the substrate applied with the hard coating are small, which can reduce the negative impact of long-term wear accumulation on the product and has excellent dimensional stability before and after the corresponding process, thereby ensuring that the product has the characteristics of low wear, high precision retention and long life.

[0055] In the present invention, carbon-doped molybdenum disulfide may be understood as molybdenum disulfide doped in a carbon-based coating, wherein the carbon-based coating may optionally include GLC.

[0056] Among them, GLC is a type of carbon-based coating, which is a carbon-based coating obtained by magnetron sputtering of graphite target.

[0057] In some embodiments of the present invention, the carbon in the carbon-doped molybdenum disulfide is derived from graphite.

[0058] In some embodiments of the present invention, the outer layer is called a friction-reducing and wear-resistant layer, and the inner layer is called a transition layer, which is applied to the substrate and has a structure such as Figure 1 shown.

[0059] In some embodiments of the present invention, the outer layer has the following element composition, in atomic percentage: C: 50-80%, Mo: 15-30%, S: 4-12%, and the remaining elements are less than 10%.

[0060] Here, the remaining elements refer to other impurity elements that are inevitably present in the outer layer.

[0061] It can be understood that, in terms of atomic percentage, the carbon content of the elements in the outer layer can be 60%, 62%, 64%, 65%, 67% or 70%; the molybdenum content can be 15%, 18%, 20%, 22%, 24%, 25%, 26% or 30%; and the sulfur content can be 4%, 5%, 6%, 7%, 8% or 10%.

[0062] In some embodiments of the present invention, the outer layer has the following element composition, calculated by atomic percentage: C: 60-70%, Mo: 20-25%, S: 5-10%, and the remaining elements are less than 10%. In some specific embodiments of the present invention, the remaining elements have a content of 4-6% by atomic percentage. In some examples of the present invention, the outer layer has the following element composition, calculated by atomic percentage: C: 60-70%, Mo: 20-25%, S: 5-10%, and the remaining elements are 4-6%.

[0063] In the hard coating, the outer layer plays a role in reducing friction and resisting wear. It is required to have moderate hardness, low friction coefficient and low wear. Therefore, the relative content of each element in the outer layer is particularly important. The content of Mo and S corresponds to the content of molybdenum disulfide. The main component of the outer layer is carbon-doped molybdenum disulfide. The content changes of the two are relative. When the content of Mo and S increases, the content of C decreases. However, carbon and molybdenum disulfide have different main effects on the hardness, friction coefficient and wear rate of the outer layer. Since carbon-based coatings generally have higher hardness and good wear resistance, but the friction coefficient is higher than that of molybdenum disulfide coatings, while molybdenum disulfide has a lower friction coefficient but also a lower hardness, the higher the carbon content, that is, the higher the C content, the higher the hardness, the better the wear resistance, the lower the wear rate, but the friction coefficient is relatively high; the higher the content of molybdenum disulfide, the lower the friction coefficient (i.e., friction reduction), but it is not good for hardness, that is, it is not good for wear rate. Therefore, by adjusting the contents of C, Mo and S elements, the relationship between friction reduction and wear resistance can be better balanced, the friction reduction and wear resistance effects can be fully exerted, and the life and precision retention of the substrate with the hard coating applied can be improved.

[0064] In some embodiments of the present invention, the thickness of the outer layer is 2-3 μm. It is understandable that the thickness of the outer layer may be 2 μm, 2.5 μm or 3 μm.

[0065] In some embodiments of the present invention, the thickness of the inner layer is 0.5-1 μm. It is understood that the thickness of the outer layer can be 0.5 μm, 0.6 μm, 0.7 μm, 0.75 μm, 0.8 μm or 1 μm. In some embodiments of the present invention, the thickness of the inner layer is 0.6-0.8 μm.

[0066] The inner layer plays a transitional role as a transition layer. Since the outer layer of the hard coating is a friction-reducing and wear-resistant layer with a relatively hard hardness, and the substrate is relatively soft when it is a flexible material, if the friction-reducing and wear-resistant layer is directly plated on the surface of the substrate material, the hardness difference between the two is too large, the bonding force is poor, and the life is short, so a transition layer is required. The hardness of the inner layer is between that of the substrate material and the outer layer, and plays a transitional role. As a transition layer, the inner layer cannot play a decisive role in the performance of the friction-reducing and wear-resistant layer, and has little effect on the performance of the hard coating. Some of the existing influences include: when the thickness of the inner layer is thin, it cannot play a transitional role, the bonding force decreases, and when it falls off, the outer layer naturally cannot play its friction-reducing and wear-resistant effect; when the inner layer is thick, it is easy to overshadow the inner layer and affect the performance of the friction-reducing and wear-resistant layer.

[0067] In some embodiments of the present invention, the thickness of the outer layer and the inner layer is obtained by measuring the cross section of the hard coating layer through scanning electron microscopy.

[0068] In some embodiments of the present invention, the metal element of the inner layer includes at least one of titanium, chromium, nickel and aluminum.

[0069] In some embodiments of the present invention, the hard coating is prepared by a magnetron sputtering process.

[0070] The hard coating prepared by magnetron sputtering process belongs to the coating coating. In the surface technology for improving the friction reduction and wear resistance of flexible parts such as flexible wheels, the coating coating is a better choice, because the processing temperature of this coating is low, and the deformation of the parts before and after the processing is small. It is especially suitable for thin-walled cylindrical parts such as flexible wheels, and has the advantages of being suitable for large-scale production. There are two major categories of materials for friction reduction and wear resistance coatings, one is carbon-based coatings (such as DLC, GLC, etc.), which are characterized by high hardness and good wear resistance, and the other is molybdenum disulfide coatings, which are characterized by good friction and lubrication performance. For flexible parts such as flexible wheels, periodic reciprocating deformation will occur during actual service, so the reliability of the bonding force between the coating and the substrate is very high, and it is difficult to take both friction reduction and wear resistance into account at the same time. The outer layer component of the present invention contains carbon-doped molybdenum disulfide, and the friction reduction and wear resistance effects are balanced by the combination of carbon and molybdenum disulfide. Further, the magnetron sputtering process can be used to obtain a coating surface technology with both friction reduction and wear resistance.

[0071] In some embodiments of the present invention, the nanoindentation hardness of the hard coating is 4 to 7 GPa.

[0072] Specifically, the nanoindentation hardness of the hard coating can be 4 GPa, 4.5 GPa, 5 GPa, 5.5 GPa, 6 GPa, 6.5 GPa or 7 GPa. In some embodiments of the present invention, the nanoindentation hardness of the hard coating is 5 to 6 GPa.

[0073] Nanoindentation hardness is a kind of nanohardness of the material itself, which is generally obtained by nanoindentation testing.

[0074] In some specific embodiments of the present invention, the nanoindentation hardness is measured using a nanoindenter under a load of 100 μN.

[0075] In some embodiments of the present invention, the hardness of the inner layer is between the hardness of the substrate and the outer layer.

[0076] In some embodiments of the present invention, the load required for the hard coating to fail cohesively or adhesively is 40 to 60 N. Optionally, the load required for the hard coating to fail adhesively is 40 N, 43 N, 45 N, 48 N, 50 N, 52 N, 55 N, 57 N or 60 N.

[0077] In the present invention, the load required for the hard coating to fail is the bonding force, and when the bonding failure occurs, the coating falls off. The higher the load required for the hard coating to fail, the better the bonding force between the hard coating and the substrate. It should be understood that the bonding failure can occur in any layer of the hard coating, which reflects the result of the failure of the bonding force. In the present invention, it mainly refers to the bonding failure of the outer layer.

[0078] In some embodiments of the present invention, the load required for the hard coating to fail is obtained by nano scratch testing.

[0079] In some embodiments of the present invention, the friction coefficient of the hard coating is 0.04 to 0.06. It is understood that in the present invention, the friction coefficient of the hard coating may be 0.04, 0.045, 0.05, 0.055, 0.058 or 0.06. In some embodiments of the present invention, the friction coefficient of the hard coating is 0.045 to 0.055.

[0080] In some embodiments of the present invention, the friction coefficient is tested under lubrication conditions. In some specific embodiments of the present invention, the lubrication condition is to add grease for harmonic reducer products.

[0081] In some embodiments of the present invention, the friction coefficient is tested by a friction and wear testing machine; in the test, the motion form of the friction pair is reciprocating motion; in the test, the load is 30N, the reciprocating frequency is 3.2Hz, the reciprocating stroke is 3mm, and the speed is 20mm / s.

[0082] The second aspect of the present invention provides a method for preparing the hard coating according to the first aspect of the present invention, comprising the following steps:

[0083] A substrate is provided, and the inner layer and the outer layer are sequentially formed on the surface of the substrate by magnetron sputtering.

[0084] The hard coating is prepared by magnetron sputtering process, which has a simple process and easy operation, avoids deformation of the substrate caused by high temperature treatment, and can successfully obtain a hard coating that is well bonded to the substrate and has friction-reducing and wear-resistant effects.

[0085] In some embodiments of the present invention, the preparation method includes the following steps: providing a substrate, forming an inner layer on the surface of the substrate by magnetron sputtering a metal target, and then simultaneously magnetron sputtering a graphite target and a molybdenum disulfide target to form an outer layer.

[0086] Specifically, in the preparation method of the hard coating of the present invention, during the inner layer coating, only the metal target works, and during the outer layer coating, the graphite target and the molybdenum disulfide target work simultaneously, and their respective bias voltages and currents can be set separately.

[0087] In some embodiments of the present invention, the target material of the inner layer magnetron sputtering includes a metal target material; the magnetron sputtering conditions of the metal target material satisfy at least one of the following a) to c):

[0088] a) DC bias voltage is 400~600V;

[0089] b) The working current is 1~3A;

[0090] c) The processing time is 1 to 2 hours.

[0091] Optionally, the DC bias voltage of the metal target may be 400 V, 450 V, 500 V, 550 V or 600 V. In some embodiments of the present invention, the DC bias voltage of the metal target may be 450 to 550 V. In some specific embodiments of the present invention, the DC bias voltage of the metal target may be 480 to 520 V.

[0092] It can be understood that the working current of the metal target can be 1A, 1.5A, 2A, 2.5A or 3A. In some embodiments of the present invention, the working current of the metal target is 1.5 to 2.5A. In some specific embodiments of the present invention, the working current of the metal target is 1.8 to 2.5A.

[0093] Furthermore, the processing time of the metal target can be 1 hour, 1.3 hours, 1.5 hours, 1.8 hours or 2 hours. In some embodiments of the present invention, the processing time of the metal target is 1.3 to 1.8 hours.

[0094] In magnetron sputtering of metal targets, voltage, current and time will affect the thickness of the inner layer. During the magnetron sputtering process, the longer the time, the thicker the inner layer will be, and the magnetron sputtering power, that is, the change in voltage or current, has a more significant effect on the change in the thickness of the inner layer. This is because higher voltage or current can increase the kinetic energy of atoms or molecules, thereby increasing the deposition rate and increasing the thickness of the inner layer.

[0095] For the outer layer, the magnetron sputtering target materials of the outer layer include graphite target materials and molybdenum disulfide target materials. Based on the same theory, the magnetron sputtering conditions of the graphite target materials and molybdenum disulfide target materials of the outer layer will also affect the thickness of the outer layer. The thickness of the inner layer affects the bonding strength between the hard coating and the substrate, and the thickness of the outer layer affects the wear-reducing and wear-resistant effect of the hard coating. Therefore, the magnetron sputtering conditions of the graphite target materials and molybdenum disulfide target materials are further controlled.

[0096] In some embodiments of the present invention, the target material for magnetron sputtering of the outer layer includes a graphite target material; the magnetron sputtering conditions of the graphite target material satisfy at least one of the following d) to f):

[0097] d) The pulse bias voltage is 300-500V;

[0098] e) The working current is 1~2A;

[0099] f) The processing time is 3 to 5 hours.

[0100] Specifically, in the present invention, the pulse bias voltage of the graphite target can be 300 V, 350 V, 380 V, 400 V, 420 V, 450 V or 500 V. In some embodiments of the present invention, the pulse bias voltage of the graphite target is 350 to 450 V. In some specific embodiments of the present invention, the pulse bias voltage of the graphite target is 380 to 420 V.

[0101] Optionally, the operating current of the graphite target may be 1 A, 1.2 A, 1.5 A, 1.8 A or 2 A. In some embodiments of the present invention, the operating current of the graphite target may be 1.2-1.8A.

[0102] Further, the processing time of the graphite target can be 3h, 3.5h, 4h, 4.5h or 5h. In some embodiments of the present invention, the processing time of the graphite target can be 3.5 to 5h. In some specific embodiments of the present invention, the processing time of the graphite target can be 3.5 to 4h.

[0103] In some embodiments of the present invention, the target material for magnetron sputtering of the outer layer further comprises a molybdenum disulfide target material; the magnetron sputtering conditions of the molybdenum disulfide target material satisfy at least one of the following g) to i):

[0104] g) The pulse bias voltage is 300-500V;

[0105] h) The working current is 0.2~1A;

[0106] i) The processing time is 3 to 5 hours.

[0107] It can be understood that the pulse bias voltage of the molybdenum disulfide target can be selected from at least one voltage of 300 V, 350 V, 380 V, 400 V, 420 V, 450 V, and 500 V. In some embodiments of the present invention, the pulse bias voltage of the molybdenum disulfide target is 350 to 450 V. In some specific embodiments of the present invention, the pulse bias voltage of the molybdenum disulfide target is 380 to 420 V.

[0108] Optionally, the operating current of the molybdenum disulfide target may be 0.2A, 0.3A, 0.5A, 0.6A, 0.8A or 1A. In some embodiments of the present invention, the operating current of the molybdenum disulfide target may be 0.5-1A. In some specific embodiments of the present invention, the operating current of the molybdenum disulfide target may be 0.5-0.8A.

[0109] Further, the processing time of the graphite target can be 3h, 3.5h, 4h, 4.5h or 5h. In some embodiments of the present invention, the processing time of the graphite target can be 3.5 to 5h. In some specific embodiments of the present invention, the processing time of the graphite target can be 3.5 to 4h.

[0110] For graphite target and molybdenum disulfide target, since the outer layer of the hard coating is carbon-doped molybdenum disulfide, the two targets are magnetron sputtered at the same time, and the processing time is the same. At the same time, since the carbon content and the molybdenum disulfide content in carbon-doped molybdenum disulfide will further affect the balance between the friction reduction effect and the wear resistance effect, that is, the balance between the hardness, friction coefficient, and wear rate, by controlling the voltage and current of the two targets, the carbon and molybdenum disulfide contents can also be adjusted to improve the friction reduction and wear resistance effect of the friction reduction and wear resistance layer. The principle of this adjustment process is described as follows:

[0111] In the magnetron sputtering process, the graphite target sputters out a GLC coating (carbon-based coating), which is characterized by very high hardness and good wear resistance, but general lubrication performance. The molybdenum disulfide target sputters out a molybdenum disulfide coating, which is characterized by good lubrication performance, but is relatively soft and has general wear resistance. The present invention forms a carbon-doped molybdenum disulfide layer by sputtering a graphite target and a molybdenum disulfide target at the same time, combining the advantages of the GLC coating and the molybdenum disulfide coating, but avoiding their respective defects. If the voltage and current of the graphite target are relatively increased during the magnetron sputtering process, the relative content of the carbon element in the outer layer is increased, the hardness of the outer layer is increased, the wear rate is reduced, but the friction coefficient is also increased. On the contrary, if the voltage and current of the molybdenum disulfide target are relatively increased, the relative content of the molybdenum disulfide in the outer layer is increased, the hardness of the outer layer is reduced, the wear rate is increased, and the friction coefficient is reduced by comparison. Therefore, by adjusting the voltage and current of the two target materials, the relative proportion of the two components in the final outer layer can be controlled, thereby better balancing the friction reduction and wear resistance effects.

[0112] In some embodiments of the present invention, the substrate is selected from a flexible spline or an alloy structural steel. It is understandable that when the substrate is an alloy structural steel, the alloy structural steel can be any shape that can be obtained by a person skilled in the art, such as a rectangle, a square, a round cake, an ellipse, etc. Further, the substrate can be a flexible spline, or a round cake-shaped substrate made of SNCM439.

[0113] In some embodiments of the present invention, the substrate further includes cleaning and pretreatment steps before being used in the magnetron sputtering process.

[0114] In some embodiments of the present invention, the cleaning process includes the following steps: cleaning the substrate with a solvent and then drying. In some specific embodiments of the present invention, the solvent includes acetone and / or anhydrous ethanol; the cleaning time is 10 to 30 minutes. It is understood that the cleaning time is not limited to 10 to 30 minutes, or any value within 10 to 30 minutes, as long as the purpose of cleaning is achieved and the grease and pollutants on the surface of the substrate are removed.

[0115] In some embodiments of the present invention, the pretreatment includes the following steps: placing the substrate on a workbench, applying a pulse bias voltage of 300 to 500 V, and treating for 30 to 60 minutes to ionize and generate plasma. In this process, the settings of the pulse bias voltage and the treatment time are all for ionization to form plasma. Those skilled in the art should understand that the pulse bias voltage and the treatment time can be arbitrarily selected within the range as long as the purpose of generating plasma is achieved. In some specific embodiments of the present invention, the pretreatment ionizes argon gas to generate plasma. During the pretreatment process, the generated plasma collides with the surface of the target material under the acceleration of the magnetron sputtering electric field, causing the target atoms to be sputtered out. Therefore, the amount and energy of the plasma will also affect the sputtering efficiency.

[0116] In some embodiments of the present invention, the equipment used in the magnetron sputtering process is first subjected to a vacuum treatment. In some specific embodiments of the present invention, the vacuum degree after the vacuum treatment is less than 1×10 -3 In some specific embodiments of the present invention, after the vacuum treatment, argon gas is introduced. In some examples of the present invention, the pressure of the argon gas after the introduction is 0.2-0.3 Pa.

[0117] In some specific embodiments of the present invention, the pretreatment is performed after vacuuming.

[0118] The third aspect of the present invention provides a flexible wheel, the surface of which is provided with the hard coating as described in the first aspect of the present invention, or the hard coating obtained by the preparation method described in the second aspect of the present invention.

[0119] For general rigid mechanical parts, they will not deform or deform very little during operation or when rubbing against other parts. Therefore, by coating the surface with a high-hardness coating, the wear resistance and life span can be significantly improved. However, this method is not feasible for flexible parts such as flexible wheels. Figure 3The figure is a physical picture of a flexible wheel, which has a hat shape. The tooth surface part of the barrel wall area is the main source of wear. This area is very thin, and the thinnest part is only about 0.2mm. The flexible wheel is a flexible part, which is always deformed during service. When not assembled, the opening in the middle of the flexible wheel is circular, but it will always undergo a circular-elliptical-circular-elliptical cyclic deformation process during service. Therefore, it is difficult to withstand such a long-term reciprocating deformation if a high-hardness coating is directly plated on the surface of the flexible wheel, and the service life will be very low. The hard coating of the present invention includes an inner layer with a transition effect and an outer layer with a friction-reducing and wear-resistant effect. The outer layer contains carbon-doped molybdenum disulfide, which has the advantages of high hardness, low wear and low friction coefficient, and has good bonding with the substrate. It is applied to the surface treatment of the flexible wheel, and the obtained flexible wheel has a small friction coefficient and a low wear rate, which can reduce the negative impact of long-term wear accumulation on the product, and has excellent dimensional stability, ensuring that the product has the characteristics of high efficiency, low wear, high precision retention and long life.

[0120] A fourth aspect of the present invention provides a harmonic reducer, comprising the hard coating described in the first aspect of the present invention, or the flexible spline described in the third aspect of the present invention.

[0121] The harmonic reducer contains a hard coating, which is applied to the flexible wheel. During the operation of the harmonic reducer, the hard coating has moderate hardness and anti-friction and wear-resistant effects, and is not easy to fall off, which effectively reduces the wear rate of the flexible wheel parts and reduces the accuracy degradation rate after durability, so that the harmonic reducer has the characteristics of long life, low wear and high precision retention.

[0122] In some embodiments of the present invention, the endurance life of the harmonic reducer is greater than 8000 hours.

[0123] In some embodiments of the present invention, the accuracy degradation rate of the harmonic reducer after durability is less than 40%.

[0124] The fifth aspect of the present invention provides an industrial robot joint component, comprising the hard coating described in the first aspect of the present invention, or the flexible spline described in the third aspect of the present invention, or the harmonic reducer described in the fourth aspect of the present invention.

[0125] The hard coating of the present invention can be applied to the flexible wheel and applied to the harmonic reducer product. The harmonic reducer is the core component of the industrial robot, and its quality level directly determines the performance of the robot joint. The performance of the harmonic reducer mainly includes two aspects: one is the durability life, that is, how long it can operate normally in the robot system. The current industry level is generally around 4000h. This indicator is related to wear. During use, wear is inevitable. If the wear continues to accumulate, it will reach a critical point. If it exceeds this critical point, the harmonic reducer product will fail and cannot be used; the other is the accuracy degradation rate, which is the relative percentage of the difference in accuracy performance before and after durability. Because the main function of the harmonic reducer in the robot is positioning accuracy, for example, it affects whether a mechanical arm can accurately position when grabbing parts or positioning. As the use time of the harmonic reducer increases, inevitable wear will occur between the harmonic reducer parts (flexible wheels), thereby affecting the positioning accuracy of the robot. Therefore, the hard coating of the present invention improves the durability of the flexible wheel or harmonic reducer and the accuracy degradation rate after durability. For industrial robots, the improvement of these performances is beneficial to the improvement of their service life and positioning accuracy.

[0126] In some embodiments of the present invention, the joints include wrists, hands, upper and lower arms, and finger joints.

[0127] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used below can be obtained from conventional commercial sources. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0128] Unless otherwise specified, the raw materials used in the following examples / comparative examples are commercially available products and are used directly without further treatment.

[0129] The substrate of the following examples can be a flexible spline obtained by a conventional preparation process, or a round substrate with a diameter of 50 mm and a thickness of about 10 mm. Both substrates are made of SNCM439, and when the substrate is a flexible spline, the material and preparation process of the flexible spline are the same as those of Comparative Example 1. In subsequent different test processes, different substrates are selected to prepare hard coatings on the surface using the same preparation method.

[0130] Example 1

[0131] Embodiment 1 provides a hard coating, including an inner layer and an outer layer; the inner layer is composed of metallic titanium, and the outer layer is composed of carbon-doped molybdenum disulfide; the inner layer is close to the surface of the substrate.

[0132] The inner layer is called the transition layer and the outer layer is called the friction-reducing and wear-resistant layer.

[0133] The specific parameters of the element composition of the outer layer are shown in Table 1.

[0134] The preparation method of the hard coating comprises the following steps:

[0135] S1. Cleaning: Use acetone or anhydrous ethanol solvent to ultrasonically clean the substrate for 10 to 30 minutes to remove surface grease and pollutants, and then load it onto the equipment fixture after drying;

[0136] S2. Vacuuming: Vacuum the equipment until the vacuum degree is <1×10 -3 Pa, then argon is introduced, and the pressure is controlled between 0.2 and 0.3 Pa;

[0137] S3. Pretreatment: Pretreatment of the substrate, the workbench pulse bias voltage is 300 to 500 V, and the treatment time is 30 to 60 min to ionize the argon gas to form a plasma;

[0138] S4. Transition layer coating: The substrate is subjected to transition layer coating treatment, the metal target material DC bias voltage is 400-600V, the working current is 1.5-2.5A, and the treatment time is 1-2h; the metal target material is a titanium target material;

[0139] S5. Anti-friction and wear-resistant layer coating: The substrate coated with the transition layer is subjected to anti-friction and wear-resistant layer coating. The graphite target is subjected to a pulse bias of 300-500V and a working current of 1.0-2.0A. The molybdenum disulfide target is subjected to a pulse bias of 300-500V and a working current of 0.2-1.0A. The treatment time is 3-5h. After the treatment, the material is taken out after cooling to room temperature. Among them, the graphite target is sputtered to form GLC, and the molybdenum disulfide target is sputtered to form MoS2, which constitute the outer layer of carbon-doped molybdenum disulfide, and is a carbon-based doped molybdenum disulfide coating.

[0140] The specific parameters of the preparation method are shown in Table 2.

[0141] Embodiments 2 to 5 provide a hard coating, including an inner layer and an outer layer; the inner layer is composed of metallic titanium, and the outer layer is composed of carbon-doped molybdenum disulfide; the inner layer is close to the surface of the substrate;

[0142] The inner layer is called the transition layer and the outer layer is called the friction-reducing and wear-resistant layer.

[0143] The differences from Example 1 are shown in Table 1.

[0144] The preparation methods of the hard coatings of Examples 2 to 5 are the same as that of Example 1, and the differences are shown in Table 2.

[0145] Comparative Example 1

[0146] The comparative example provides a flexspline which is obtained by a conventional method and is not subjected to a hard coating or other surface treatment.

[0147] In Examples 1 to 5, the element composition of the friction reducing and wear resistant layer (i.e., the outer layer) was measured by referring to the following method:

[0148] The substrate (SNCM439 material in the shape of a round cake with a diameter of 50 mm and a thickness of about 10 mm) with a hard coating was measured with an X-ray photoelectron spectroscopy (XPS) tester to obtain the element content based on atomic percentage. XPS measures the electron binding energy of an element to determine the type and chemical state of the element. By comparing the peak area of ​​each element, the atomic percentage of each element can be calculated.

[0149] The following is a table of hard coating parameters and a table of preparation method parameters for Examples 1 to 5.

[0150] Table 1 Element composition parameters of the outer layer of the hard coating of Examples 1 to 5 (in atomic percentage)

[0151] Sample Example 1 Example 2 Example 3 Example 4 Example 5 C content / at.% 65 65 60 70 65 Mo content / at.% 23 23 25 20 23 S content / at.% 7 7 10 5 7 Other elements content / at.% 5 5 5 5 5

[0152] Table 2 Parameters of the hard coating preparation method of Examples 1 to 5

[0153]

[0154] The hard coatings of the above-mentioned Examples 1 to 5 and the flexspline containing the hard coatings are tested for performance, and the flexspline of Comparative Example 1 is tested for the same performance. In different test methods, different substrates are selected, mainly flexsplines or disc-shaped substrates made of SNCM439. It should be understood that, since in the test process, whether the substrate is a flexspline or a disc-shaped substrate, the material is the same, and the hard coating has the same characteristic parameters under the same preparation parameters, and the friction and wear process mainly occurs on the surface of the hard coating, even if the performance obtained by testing the disc-shaped substrate, such as friction coefficient, wear rate, and bonding force, should be considered that the hard coating on the flexspline substrate also shows a considerable effect.

[0155] The specific test method is as follows:

[0156] 1. Thickness of anti-friction and wear-resistant layer and transition layer

[0157] The substrates (round cake-shaped with a diameter of 50 mm and a thickness of about 10 mm, made of SNCM439) to which the hard coatings of Examples 1 to 5 were applied were cut in cross section and observed using a scanning electron microscope (SEM). Different layers can be clearly observed, such as the Figure 2 As shown, the thickness of the transition layer and the thickness of the friction-reducing and wear-resistant layer can be obtained by measuring the different layers in the SEM image.

[0158] The thickness of the transition layer and the thickness of the friction-reducing and wear-resistant layer of the hard coating of Examples 1 to 5 are shown in Table 3.

[0159] Table 3 Transition layer thickness and anti-friction wear layer thickness of the hard coating of Examples 1 to 5

[0160] Sample Example 1 Example 2 Example 3 Example 4 Example 5 Transition layer thickness / μm 0.75 0.75 0.75 0.75 0.75 Thickness of anti-friction and anti-friction layer / μm 2 3 2.5 2.5 2.5

[0161] 2. Nanoindentation hardness of friction-reducing and wear-resistant layer

[0162] The substrate (disk-shaped with a diameter of 50 mm and a thickness of about 10 mm, made of SNCM439) with a hard coating was subjected to a nanoindentation tester, and a load of 100 μN was applied and the indentation depth was measured to obtain the nanoindentation hardness.

[0163] The nanoindentation hardness of the friction reducing and wear resistant layers of Examples 1 to 5 is shown in Table 4.

[0164] Table 4 Nanoindentation hardness of the friction-reducing and wear-resistant layers of Examples 1 to 5

[0165] Sample Example 1 Example 2 Example 3 Example 4 Example 5 Hardness / GPa 5.5 5.5 5.0 6.0 5.5

[0166] 3. The bonding strength between hard coating and substrate

[0167] The substrate with hard coating (round cake with a diameter of 50mm and a thickness of about 10mm, made of SNCM439) was tested using a nano scratch measuring instrument. The wear process of the coating was simulated by control and monitoring, and the load required to cause the adhesion failure of the hard coating was measured, and the bonding force in N was obtained.

[0168] The test results of the bonding strength between the hard coating and the substrate in Examples 1 to 5 are shown in Table 5.

[0169] Table 5 Binding strength between the hard coating and the substrate of Examples 1 to 5

[0170]

[0171]

[0172] It can be seen from Tables 3 to 5 that the hard coatings of Examples 1 to 5 of the present invention have good bonding strength with the substrate, and the bonding strength is not less than 45N. It can be seen from the comparison between Examples 1 and 2 that the thickness of the outer anti-friction and wear-resistant layer changes, but when the thickness of the inner transition layer remains unchanged, there is almost no effect on the bonding strength between the hard coating and the substrate. In Examples 3 to 5, the content of each element in the anti-friction and wear-resistant layer changes, and when the thickness remains unchanged, the hardness changes, and the bonding strength with the substrate also changes, which shows that the composition of the anti-friction and wear-resistant layer not only affects the friction reduction and wear resistance effect, but also causes the bonding strength to change.

[0173] Comparative Example 1 is an untreated original flexible spline, which is manufactured according to the conventional manufacturing process, and the surface is not subjected to coating treatment, so there is no data on coating thickness, hardness, and bonding strength.

[0174] 4. Friction coefficient and wear rate of hard coating

[0175] The substrates (round cakes with a diameter of 50 mm and a thickness of about 10 mm, made of SNCM439) or the flexible wheel of comparative example 1 applied with hard coating in Examples 1 to 5 were clamped on a standard friction and wear tester for testing. The friction pair was a steel ball made of GCr15 material and a diameter of 12.7 mm. The friction pair motion was reciprocating motion. The lubrication conditions were adding grease for harmonic reducer products, the load was 30 N, the speed was 20 mm / s, the reciprocating frequency was 3.2 Hz, the reciprocating stroke was 3 mm, the temperature was room temperature, and the time was 10 min. During the test, the instrument automatically recorded the corresponding friction coefficient. After the test, the sample was observed under a laser confocal microscope, and the wear volume was obtained by contour scanning, and then the corresponding wear rate could be calculated. The specific calculation formula is as follows:

[0176] Wear rate = wear volume / (normal load × sliding distance); K represents the wear rate, V represents the wear volume, F represents the normal load, and s represents the sliding distance, then the formula is K = V / (F × s).

[0177] The friction coefficient and wear rate of the hard coatings of Examples 1 to 5 and Comparative Example 1 are shown in Table 6.

[0178] Table 6 Friction coefficient and wear rate of hard coatings of Examples and Comparative Examples

[0179] Sample Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Friction coefficient 0.05 0.05 0.045 0.055 0.05 0.15 <![CDATA[Wear rate (mm 3 / Nm)]]> <![CDATA[1×10 -7 ]]> <![CDATA[1×10 -7 ]]> <![CDATA[1.2×10 -7 ]]> <![CDATA[8×10 -8 ]]> <![CDATA[1×10 -7 ]]> <![CDATA[2×10 -6 ]]>

[0180] It can be seen from Table 6 that the friction coefficient of the flexible wheel without coating treatment in Comparative Example 1 is higher than that of Examples 1 to 5, which is about three times that of Examples 1 to 5, and the wear rate is at least one order of magnitude higher than that of Examples 1 to 5. Obviously, the hard coatings of Examples 1 to 5 of the present invention have significant effects on friction reduction and wear resistance, and have the advantages of low wear and low friction coefficient.

[0181] Since the flexible wheel parts in comparative example 1 are not treated with coating, their friction coefficient and wear rate levels are equivalent to conventional parameter levels, and the corresponding durability and precision degradation rates are also at the current general level. The present invention introduces a hard coating, which improves the wear-reducing and wear-resistant performance of the product, improves the durability of the product, and enhances the precision retention of the product while ensuring that the structural dimensions and other factors of the substrate remain unchanged.

[0182] 5. Durable life of flexible wheel

[0183] The substrates (substrates are flexible wheels) with hard coatings in Examples 1 to 5 and the flexible wheel in Comparative Example 1 were assembled into harmonic reducer products to verify the bench life of the whole product. The entire experimental process was an accelerated durability test under the following conditions: temperature 25°C, humidity controlled at less than 35%, and conducted on a customized durability bench for harmonic reducers. The final result is the equivalent durability time of the harmonic reducer product in h.

[0184] The durability life of the flexible splines of the embodiments and comparative examples is shown in Table 7.

[0185] Table 7 Durability of the flexible wheel of the embodiment and the comparative example

[0186] Sample Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Durable life / h >8000 >8000 >12000 >8000 >10000 >4000

[0187] It can be seen from Table 7 that the durable life of the flexible splines containing the hard coating of the present invention in Examples 1 to 5 is at least twice that of Comparative Example 1, and the durable life is not less than 8000 hours, while the untreated flexible spline in Comparative Example 1 is only at the general level of 4000 hours.

[0188] 6. Precision degradation rate of flexible wheel after durability

[0189] The substrates (substrates are flexible plies) with hard coatings applied in Examples 1 to 5 and the flexible ply of Comparative Example 1 are assembled into harmonic reducer products. The accuracy performance of the harmonic reducer products before durability is first tested. If the value is a, the unit is arc*sec. Then, the product is subjected to a whole machine bench life verification under the same conditions as the fifth durability life test. After the life test is completed, the accuracy performance of the product after durability is retested. If the value is b, the unit is arc*sec, then 100×(ab) / a is the accuracy degradation rate of the product after durability, in %.

[0190] The accuracy degradation rates of the flexible wheel products of Examples 1 to 5 and Comparative Example 1 after durability are shown in Table 8.

[0191] Table 8 Precision degradation rate of flexible wheels in embodiments and comparative examples

[0192] Sample Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Accuracy degradation rate / % <40 <20 <40 <20 <30 >50

[0193] In Table 8, the accuracy degradation rate of the harmonic reducer using the flexible wheel of Comparative Example 1 after durability is more than 50%, while the accuracy degradation rate of Examples 1 to 5 does not exceed 40%, which has excellent accuracy retention.

[0194] The test results of the above-mentioned Examples 1 to 5 and Comparative Example 1 are further specifically analyzed as follows:

[0195] By comparing Examples 1 to 5 with Comparative Example 1, it can be seen that no matter which embodiment, compared with Comparative Example 1, it is superior to Comparative Example 1 in terms of friction coefficient and wear rate, durability life and precision degradation rate, indicating that the overall effect of the embodiments of the present invention is better than that of Comparative Example 1.

[0196] Combining Tables 1 to 4 and Table 6, the changes in hardness, friction coefficient and wear rate are analyzed as follows:

[0197] The main component of the hard coating formed in Examples 1 to 5 is carbon, that is, it is mainly a carbon-based coating GLC, doped with molybdenum disulfide, and has a relatively high hardness. At this time, the changes in the friction coefficient and wear rate are related to the relative content of carbon and molybdenum disulfide. Compared with the molybdenum disulfide coating, the carbon-based coating has a larger friction coefficient. Therefore, the introduction of molybdenum disulfide is beneficial to reducing the friction coefficient. However, due to the low hardness of molybdenum disulfide, a part of the hard coating will be sacrificed at this time, which leads to a situation where the friction coefficient decreases when the hardness increases.

[0198] By comparing Examples 1 to 5, it can be seen that there are differences in the test results between different Examples.

[0199] In combination with Example 1, Example 2 and Example 5, the three examples are analyzed as follows:

[0200] From the aspect of preparation parameters, comparing Example 1, Example 2 and Example 5, the voltage and current of the graphite target and the molybdenum disulfide target of the three are the same, and only the processing time of magnetron sputtering is changed. The thickness of the obtained anti-friction wear-resistant layer is significantly different, while the hardness and element composition are the same. This is because the relative power of the two targets determines the relative proportion of GLC (carbon-based coating) and MoS2 in the prepared anti-friction wear-resistant layer, that is, the ratio of carbon to molybdenum disulfide, which in turn determines the hardness of the anti-friction wear-resistant layer. When the power remains unchanged, that is, the voltage and current are different, and only the processing time is changed, the ratio of carbon to molybdenum disulfide does not change. The thickness of the anti-friction wear-resistant layer is affected by the processing time. The longer the time, the higher the thickness, but this does not affect the hardness. This is because the hardness in the present invention is measured at the nanoscale on the surface of the anti-friction wear-resistant layer. As long as the composition and component percentage of the anti-friction wear-resistant layer are consistent, the hardness will remain consistent.

[0201] In terms of bonding strength, the bonding strength between the hard coatings of Examples 1 and 2 and the substrate is worse than that of Example 5, which indicates that the parameter conditions of Example 5 are actually further optimizations of the hard coating of the present invention. By comparing Example 1, Example 2 and Example 5, it can be seen that the friction-reducing and wear-resistant layer cannot be too thin or too thick. When the friction-reducing and wear-resistant layer is too thin, it is easier to be scratched when the bonding strength is measured by a nanoindentation measuring instrument, that is, the bonding strength is reduced. However, when the thickness of the friction-reducing and wear-resistant layer is too thick, the internal stress level inside the friction-reducing and wear-resistant layer is high, and the bonding strength is also reduced. It should be noted that in the process of preparing the hard coating by magnetron sputtering, internal stress will inevitably be introduced into the coating. The internal stress should be controlled at a lower level as much as possible. Excessive voltage, current and processing time, and excessive thickness will cause an increase in internal stress.

[0202] In terms of friction coefficient and wear rate, the performance of the hard coating itself is mainly tested, so the hard coating will not be damaged during the entire experiment. The hardness of the friction-reducing and wear-resistant layers of Example 1, Example 2 and Example 5 is equivalent. When the hard coating is not damaged, the friction coefficient and wear rate of the three are basically the same. At the same time, although the thickness of the friction-reducing and wear-resistant layers in Example 1, Example 2 and Example 5 is different, they can withstand the friction performance test without being damaged within the range of 2 to 3 μm, so the thickness has little effect on the friction coefficient and wear rate. When the hard coating is too thin, or when the outer friction-reducing and wear-resistant layer of the hard coating is too thin, such as only 0.5 μm, the hard coating will be damaged during the test, which will lead to a worse wear rate.

[0203] Judging from the performance results of the harmonic reducer products, since the bonding strength levels of the hard coatings of Examples 1 and 2 are lower than that of Example 5, the durability level is slightly worse. In terms of precision retention, the anti-friction and wear-resistant layers of the three embodiments have similar hardness and wear resistance. In this case, the thicker the coating, the more it is worn away after durability. Although the absolute values ​​are close, in relative values, the thicker the coating, the more complete the coating that remains unworn after durability. Therefore, the corresponding precision retention level is relatively better.

[0204] Comparative Example 3, Example 4 and Example 5, the following analysis is performed in combination with the three examples:

[0205] In the hard coatings of Examples 3 to 5, the thickness of the friction-reducing and wear-resistant layer remains unchanged, all at 2.5 μm, but the hardness of the friction-reducing and wear-resistant layer varies. Relative to Example 5, the hardness of the friction-reducing and wear-resistant layer in Example 4 increases, and accordingly, it is necessary to increase the proportion of carbon in the friction-reducing and wear-resistant layer and reduce the proportion of molybdenum disulfide. In the preparation process, from the perspective of preparation parameters, the embodiments of the present invention are reflected in that the parameters of the molybdenum disulfide target remain unchanged, and the sputtering power of the graphite target is increased, such as increasing the current. At the same time, in order to keep the thickness of the friction-reducing and wear-resistant layer at 2.5 μm, due to the increase in the power of the overall magnetron sputtering, the processing time needs to be appropriately reduced. The hardness of the friction-reducing and wear-resistant layer in Example 3 is relatively low, and the logic of its parameter changes is the same as that in Example 4.

[0206] In terms of bonding strength, the thickness of the friction-reducing and wear-resistant layers of Examples 3 to 5 is 2.5 μm, so the influence of the thickness factor can be basically ignored. However, the hardness of the friction-reducing and wear-resistant layers of Examples 3 to 5 is different. The hardness of Example 4 is higher. The higher the hardness of the friction-reducing and wear-resistant layer, the worse the bonding strength with the substrate and the transition layer will be. The entire hard coating shows a lower bonding strength with the substrate, and vice versa. Therefore, the bonding strength of Example 4 is lower, and the bonding strength of Example 3 is higher.

[0207] In terms of friction coefficient and wear rate, it is mainly affected by the hardness of the anti-friction and wear-resistant layer. When the hardness of the anti-friction and wear-resistant layer is higher, the wear rate is lower. However, at this time, the content of molybdenum disulfide, that is, the content of Mo and S is relatively reduced, so the friction reduction performance will be worse, that is, the friction coefficient will increase, and vice versa. These rules are essentially directly related to the relative proportion of carbon and molybdenum disulfide. The carbon-based coating (GLC) has good wear resistance but average friction reduction performance. The molybdenum disulfide coating reduces friction but is not wear-resistant. It is necessary to take both into account and balance.

[0208] In terms of harmonic reducer products, compared with Example 5, the hardness of the anti-friction and wear-resistant layer of Example 3 is lower, and the bonding force between the overall hard coating and the substrate flexible wheel is better. Therefore, after being applied to the harmonic reducer, the product has a longer durable life, but a higher wear rate, so the precision degradation rate is also increased; and compared with Example 5, the hardness of the anti-friction and wear-resistant layer of Example 4 is higher, and the bonding force is relatively poor, so the durable life is shorter, but the wear resistance is better and the wear rate is lower, so the precision degradation rate is lower, that is, the precision retention is higher.

[0209] Through the above analysis of Examples 1 to 5, it can be seen that in the hard coating, the anti-friction and wear-resistant performance is mainly affected by the thickness, composition and proportion of the outer anti-friction and wear-resistant layer, that is, it is affected by the ratio of carbon and molybdenum disulfide. The carbon-based coating has a higher hardness, and the molybdenum disulfide coating has a lower hardness. The two are hard and soft, so the ratio of the two affects the hardness of the anti-friction and wear-resistant layer, and then affects the friction coefficient, wear rate, and bonding force, and ultimately affects the durability and precision retention of the harmonic reducer. The hardness and thickness of the anti-friction and wear-resistant layer will affect the bonding force. At the same time, the bonding force will also be affected by the thickness of the inner transition layer. When the thickness of the anti-friction and wear-resistant layer can meet the basic requirements, the friction coefficient and wear rate are mainly affected by the hardness and composition ratio of the anti-friction and wear-resistant layer. For harmonic reducer products, the durable life is mainly affected by the bonding force, and the precision degradation rate is mainly affected by the wear rate.

[0210] In the preparation process of hard coating, magnetron sputtering process is adopted. The relative size of voltage and current of graphite target and molybdenum disulfide target will affect the relative proportion of carbon and molybdenum disulfide in the anti-friction and wear-resistant coating, while the processing time of different targets affects the thickness of transition layer and anti-friction and wear-resistant layer.

[0211] In summary, the hard coating of the present invention has excellent friction reduction and wear resistance effects. The hard coating can not only make the substrate have excellent dimensional stability before and after the coating process, but also has good bonding force with the substrate and is not easy to fall off in actual work. It can be applied to the flexible wheel to effectively reduce the wear rate of the flexible wheel, so that the harmonic reducer product has the advantages of long life, low wear, high precision retention, etc.

[0212] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A hard coating, characterized in that: The hard coating is arranged on a substrate, and comprises an inner layer and an outer layer arranged in sequence; the composition of the inner layer comprises metal elements, and the composition of the outer layer comprises carbon-doped molybdenum disulfide; the inner layer is close to the surface of the substrate.

2. The hard coating according to claim 1, characterized in that In terms of atomic percentage, the element composition of the outer layer is as follows: C: 50-80%, Mo: 15-30%, S: 4-12%, and the remaining elements are less than 10%.

3. The hard coating according to claim 1 or 2, characterized in that: The thickness of the outer layer is 2-3 μm.

4. The hard coating according to claim 1, characterized in that The thickness of the inner layer is 0.5-1 μm.

5. The hard coating according to claim 1 or 4, characterized in that: The metal element of the inner layer includes at least one of titanium, chromium, nickel and aluminum.

6. The hard coating according to claim 1 or 2, characterized in that: The nanoindentation hardness of the outer layer is 4 to 7 GPa.

7. The hard coating according to claim 1, characterized in that The load required for the hard coating to fail in adhesion is 40-60N.

8. The hard coating according to claim 1, characterized in that The friction coefficient of the hard coating is 0.04 to 0.

06.

9. A method for preparing a hard coating according to any one of claims 1 to 8, characterized in that: The steps include: A substrate is provided, and the inner layer and the outer layer are sequentially formed on the surface of the substrate by magnetron sputtering.

10. The preparation method according to claim 9, characterized in that: The target material of the inner layer magnetron sputtering includes a metal target material; the magnetron sputtering conditions of the metal target material meet at least one of the following a) to c): a) DC bias voltage is 400~600V; b) The working current is 1.5~2.5A; c) The processing time is 1 to 2 hours.

11. The preparation method according to claim 9, characterized in that: The target material for magnetron sputtering of the outer layer includes a graphite target material; the magnetron sputtering conditions of the graphite target material satisfy at least one of the following d) to f): d) The pulse bias voltage is 300-500V; e) The working current is 1~2A; f) The processing time is 3 to 5 hours.

12. The preparation method according to claim 11, characterized in that: The target material for magnetron sputtering of the outer layer further comprises a molybdenum disulfide target material; the magnetron sputtering conditions of the molybdenum disulfide target material satisfy at least one of the following g) to i): g) The pulse bias voltage is 300-500V; h) The working current is 0.2~1A; i) The processing time is 3 to 5 hours.

13. A flexible wheel, characterized in that: The surface is provided with a hard coating as claimed in any one of claims 1 to 8, or a hard coating obtained by the preparation method as claimed in any one of claims 9 to 12.

14. A harmonic reducer, characterized in that: The invention comprises the hard coating according to any one of claims 1 to 8, or the flexible wheel according to claim 13.

15. An industrial robot joint component, characterized in that: It comprises the hard coating according to any one of claims 1 to 8, or the flexible wheel according to claim 13, or the harmonic reducer according to claim 14.

Citation Information

Cited By

  • Sliding vane, manufacturing method thereof, compressor and refrigeration equipment

    CN121408216A